Prevalence and Determinants of Ideal Cardiovascular Health in Kenya: A Cross-Sectional Study Using Data From the 2015 Kenya STEPwise Survey - James Odhiambo Oguta; Penny Breeze; Elvis Wambiya; Catherine Akoth; Grace Mbuthia; Peter Otieno; Oren Ombiro; Yvette Kisaka; Lilian Mbau; Elizabeth Onyango; Gladwell Gathecha; Pete R. J. Dodd (Ubiquity Press, 2024)
Background: Kenya is experiencing a rising burden of cardiovascular diseases (CVDs) due to epidemiological and demographic shifts, along with increasing risk factors. Ideal cardiovascular health (iCVH), defined by the American Heart Association (AHA), encompasses eight metrics to evaluate cardiovascular well-being. This study assessed the prevalence and determinants of iCVH in Kenya. Methods: Data from the 2015 Kenya STEPwise survey on non-communicable disease risk factors, including 4,500 adults aged 18-69, were analysed. iCVH was assessed using 2022 AHA criteria based on seven factors: nicotine exposure, physical activity, diet, BMI, blood pressure, glucose, and lipid levels. A cardiovascular health (CVH) CVH score of ≥80% classified individuals as having iCVH. Multivariable binary and ordinal logistic regression identified factors associated with iCVH. Results: The mean CVH score in Kenya was 78.6% (95% CI: 77.9,79.2%), higher in females (79.3%), rural areas (79.5%), and non-drinkers (79.6%) than in males (77.9%), urban residents (77.0%), and alcohol drinkers (75.4%), respectively. The prevalence of iCVH (CVH score ≥80%) was 45.6%, while 6.4% had poor CVH (CVH score <50%). Only 1.2% achieved the maximum CVH score. iCVH prevalence declined with age and was lower among married individuals (43.7%), alcohol drinkers (32.3%), and urban residents (39.7%). Older adults had 50-80% lower odds of iCVH compared to those under 30 years. Alcohol users (AOR 0.5; p < 0.001) and urban residents (AOR 0.6; p < 0.001) were less likely to have iCVH. Residents of Nairobi and Central regions had 40-60% lower odds of iCVH compared to those in Rift Valley. The Kalenjin (AOR 0.5; p = 0.027) and Turkana (AOR 0.3; p = 0.002) ethnic groups had lower odds of iCVH compared to the Kisii. Conclusion: Less than half of Kenyan adults have iCVH, with poorer CVH status among older adults, urban residents, and alcohol users. Targeted public health interventions could mitigate the CVD burden and enhance health outcomes in Kenya.